The Role of CEBPD in Oxidative Stress and Angiogenesis Regulation in Endometriosis - Jing Su; Peipei Tang; Jixiang Zhong; Rongxue Zhang; Huiying Xue; Hong Zhang (Frontiers in Bioscience-Landmark)
Background: Endometriosis (EM) is a prevalent gynecological disorder in women. Although the underlying mechanisms have yet to be fully elucidated, EM may be related to oxidative stress. The current research aimed to identify possible pathways that control oxidative stress in EM, thereby providing a theoretical foundation for its clinical diagnosis and treatment. Methods: High-throughput RNA sequencing (RNA-seq) data were integrated with GeneCards online data to screen for oxidative stress-related genes and potential targets in EM. The reverse transcription-quantitative polymerase chain reaction (RT-qPCR), Western blotting, and immunohistochemistry assays confirmed the expression of candidate genes. The in vivo and in vitro effects of CCAAT enhancer binding protein delta (CEBPD, C/EBP-delta) and DNA damage-inducible transcript 4 (DDIT4) on oxidative stress, cell proliferation, and angiogenesis in endometriotic cells were validated using loss- or gain-of-function approaches. Results: CEBPD was highly expressed in ectopic and eutopic endometrial tissue from patients with endometriosis. Loss- or gain-of-function experiments showed that CEBPD promoted oxidative stress, cell proliferation, and angiogenesis in vitro and in vivo. Integration of RNA-seq and online data revealed that CEBPD regulates DDIT4 expression, subsequently increasing oxidative stress, cell proliferation, and angiogenesis in endometriotic cells. Finally, CEBPD and DDIT4 were found to regulate the expression of extracellular signal-regulated kinase 1/2 (ERK1/2) proteins associated with the mitogen-activated protein kinase (MAPK) signaling pathway. Conclusions: These results suggest that CEBPD may promote oxidative stress, cell proliferation, and angiogenesis in EM by activating MAPK via DDIT4. Hence, CEBPD may be a potential target for diagnosing and treating EM.